2022
DOI: 10.1002/psc.3456
|View full text |Cite
|
Sign up to set email alerts
|

Conjugates of adenosine mimetics and arginine‐rich peptides serve as inhibitors and fluorescent probes but not as long‐lifetime photoluminescent probes for protein arginine methyltransferases

Abstract: The conjugates of an adenosine mimetic and oligo-L-arginine or oligo-D-arginine (ARCs) were initially designed in our research group as inhibitors and photoluminescent probes targeting basophilic protein kinases. Here, we explored a panel of ARCs and their fluorescent derivatives in biochemical assays with members of the protein arginine methyltransferase (PRMT) family, focusing specifically on PRMT1. In the binding/displacement assay with detection of fluorescence anisotropy, we found that ARCs and arginine-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…Since then, numerous comparisons have been made differentiating the uptake potential of positively charged, short peptide chains against their long or net-neutral counterparts. Specifically, it was shown that short homopolymers of arginine (R) had higher uptake compared to other amino acids including polylysine chains [ 20 , 21 , 22 , 23 ]. Attempts to utilize and mimic this ability have been undertaken, achieving excellent results.…”
Section: Types Of Cppsmentioning
confidence: 99%
“…Since then, numerous comparisons have been made differentiating the uptake potential of positively charged, short peptide chains against their long or net-neutral counterparts. Specifically, it was shown that short homopolymers of arginine (R) had higher uptake compared to other amino acids including polylysine chains [ 20 , 21 , 22 , 23 ]. Attempts to utilize and mimic this ability have been undertaken, achieving excellent results.…”
Section: Types Of Cppsmentioning
confidence: 99%